PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA UNTUK MENINGKATKAN HASILBELAJAR MATEMATIKASISWA KELAS VA SD NEGERI 94 PEKANBARU - Putra, Marthin Edelweys; Syahrilfuddin, Syahrilfuddin; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the low students mathematicslearning outcomes. This can be seen from preliminary test results with an average of 64.73 while KKM 75. This research is a classroom action research, which consists of two cycles. The first cycle consists of two meetings and one daily test at the end of each cycle, and cycle II consists of two meetings and one daily test at each end of the cycle as too. The subjects of this research were students VA SD Negeri 94 Pekanbaru consisting of 24 male students and 13 female students. After the improvement of learning using PMRI approach of teacher activity in the first cycle increased from 55% with enough category, to 65% with good category. Then increase again in cycle II from 75% with good category, to 85% with very good category. While the activity of students in the first cycle increased from 55% with enough category, to 65% with good category. Then increase again in cycle II from 70% with good category, to 80% with good category. Student learning outcomes increased from 64.73 to 75.91 in daily test I and daily test II increased again to 81.99. With the application of PMRI approach there is an increase in student learning outcomes from the basic score to the daily test II of 26.66%. Thus it can be concluded the application of PMRI approach can improve the learning outcomes of students' mathematics class VA SD Negeri 94 Pekanbaru.Keywords: Indonesian realistic mathematics education approach, learning outcomes of mathematics